Pemberian Pakan Alami Alternatif Berondolan Sawit Terhadap Pertumbuhan Panjang Dan Berat Ikan Lele Sangkuriang (Clarias gariepinus var.) - Noorsheha Noorsheha; Putri Anugerah; Ricko Reynalta (Universitas Pahlawan Tuanku Tambusai, 2024)
The high cost of feed makes farmers more creative and innovative in making fish feed as an alternative feed, especially for sangkuriang catfish (Clarias gariepinus var.). Alternative natural feed can be given to reduce costs incurred during maintenance such as the results of decomposition by palm loose fruits. The purpose of this study was to determine the effect of alternative natural feeding with the palm loose fruits decay method on the growth of length and body weight of sangkuriang catfish (Clarias gariepinus var.). Palm loose fruits was taken from oil palm plantations in the Gunung Lagan area, Gunung Meriah District, Aceh Singkil Regency, Aceh Province. This type of research is a type of experimental research with the research data obtained analyzed using the one-way ANOVA test to see the differences between treatments (A) softened palm loose fruits, (B) palm loose fruits that have caterpillars on the decaying media and (C) control treatment, taken softened palm loose fruits for treatment (A) and (B) that have caterpillars, then given to catfish as much as 2 handfuls and spread evenly in the pond. For treatment (C) or control treatment, commercial feed type FF-999 is given as much as 2 handfuls. The results showed that the body weight of sangkuriang catfish in treatment A with 3 replications was 55.87 g, treatment B was 62.72 g and treatment C was 58.56 g. Meanwhile, the body length of sangkuriang catfish in treatment A with 3 replications was 12.49 cm, treatment B was 14.61 cm and treatment C was 13.55 cm. In treatment C, the average value is not much different from treatment A.